China into its second rise : myths, puzzles, paradoxes, and challenge to theory. - Hsiung, James Chieh, 1935- (World Scientific, 2012)
This book seeks to demystify the re-ascendancy of China as a civilization state. China's politics and society are examined in the light of its living civilization, which is the only one of the ancient civilizations that has survived to this day. The book also contrasts China's development with that of the West and Japan. By combining the impact of internal political and socio-economic developments in China and its external relations (from the silk routes, the tribute system, to the modern day), it unravels the existing myths, puzzles, and paradoxes surrounding China and questions the adequacy.